Bilingualism and the Latin language - Adams, J. N. (James Noel) (Cambridge University Press, 2003)
Since the 1980s, bilingualism has become one of the main themes of sociolinguistics - but there are as yet few large-scale treatments of the subject specific to the ancient world. This book is the first work to deal systematically with bilingualism during a period of antiquity (the Roman period, down to about the fourth century AD) in the light of sociolinguistic discussions of bilingual issues. The general theme of the work is the nature of the contact between Latin and numerous other languages spoken in the Roman world. Among the many issues discussed three are prominent: code-switching (the practice of switching between two languages in the course of a single utterance) and its motivation, language contact as a cause of change in one or both of the languages in contact, and the part played by language choice and language switching in the establishment of personal and group identities.